GOLD SOLUBILITY IN THE COMMON GOLD-BEARING MINERALS: EXPERIMENTAL EVALUATION AND APPLICATION TO PYRITE - Tauson V.L. (My University, 1999)
A method is proposed for determining gold solubility in the common gold-bearing minerals (sulfides, etc.) using so-called 'gold-assisting elements' (GAE). These elements increase gold solubility in the fluid phase, enabling minerals formed from hydrothermal fluids to be saturated with gold. Two experimental approaches are discussed: (1) identifying the solid-solution limit of gold in a mineral structure by determining the maximum content of uniformly distributed gold constituent which remains unchanged with increasing gold content in the coexisting fluid phase, and (2) determining the gold distribution between the mineral under study and a reference mineral with a sufficiently high and well-defined solid-solution limit of gold and utilizing the phase composition correlation principle. Statistical treatment of analytical data for single crystals permits inference of the structurally bound gold constituent. Greenockite (α-CdS) incorporates a maximum of 50 ± 7 ppm Au in solid solution at 500°C and 1 kbar and this is used as a reference mineral to determine gold solubility in pyrite under the same conditions in the presence of As and Se as gold-assisting elements. The value obtained for gold solubility in pyrite (3 ± 1 ppm Au) is in reasonable agreement with the results of ion-probe microanalysis of natural pyrites. The data suggest that monovalent gold substitutes for divalent iron, giving rise to an acceptor center compensated by a donor defect, either a sulphur vacancy or a hydrosulphide ion replacing S22-.